Estimating assistive product need in Cameroon and India: results of population‐based surveys and comparison of self‐report and clinical impairment assessment approaches. Issue 2 (3rd December 2020) - Boggs, Dorothy; Kuper, Hannah; Mactaggart, Islay; Murthy, GVS; Oye, Joseph; Polack, Sarah
Abstract: Objectives: To estimate population need and coverage for distance glasses, hearing aids and wheelchairs in India and Cameroon, and to explore the relationship between assistive product (AP) need measured through self‐report and clinical impairment assessment. Methods: Population‐based surveys of approximately 4000 people each were conducted in Mahabubnagar district, India and Fundong district, Cameroon. Participants underwent standardised vision, hearing and musculoskeletal impairment assessment to assess need for distance glasses, hearing aids, wheelchairs. Participants with moderate or worse impairment and/or self‐reported difficulties in functioning were also asked about their self‐reported AP need. Results: 6.5% (95% CI 5.4–7.9) in India and 1.9% (95% CI 1.5–2.4) in Cameroon of the population needed at least one of the three APs based on moderate or worse impairments. Total need was highest for distance glasses [3.7% (95% CI 2.8–4.7) India; 0.8% (95% CI 0.5–1.1), Cameroon] and lowest for wheelchairs (0.1% both settings; 95% CI 0.03–0.3 India, 95% CI 0.04–0.3 Cameroon). Coverage for each AP was below 40%, except for distance glasses in India, where it was 87% (95% CI 77.1–93.0). The agreement between self‐report and clinical impairment assessment of AP need was poor. For instance, in India, 60% of people identified through clinical assessment as needing distance glasses did not self‐report a need. Conversely, in India, 75% of people who self‐reported needing distance glasses did not require one based on clinical impairment assessment. Conclusions: There is high need and low coverage of three APs in two low‐and middle‐income settings. Methodological shortcomings highlight the need for improved survey methods compatible with the international classification of functioning, disability and health to estimate population‐level need for AP and related services to inform advocacy and planning. Abstract : Objectifs: Estimer les besoins et la couverture de la population en lunettes de distance, appareils auditifs et chaises roulantes en Inde et au Cameroun; et explorer la relation entre les besoins en produits d'assistance (PA) mesurés par l'auto‐déclaration et l'évaluation clinique de la déficience. Méthodes: Enquêtes de population sur environ 4.000 personnes, chacune menées dans le district de Mahabubnagar, en Inde et dans le district de Fundong, au Cameroun. Les participants ont subi une évaluation standardisée de la vision, de l'audition et des troubles musculosquelettiques pour évaluer les besoins en lunettes de distance, en appareils auditifs et en chaises roulantes. Les participants ayant une déficience modérée ou sévère et/ou des difficultés fonctionnelles autodéclarées ont également été interrogés sur leurs besoins autodéclarés en PA. Résultats: 6, 5% (IC95%: 5, 4–7, 9) de la population en Inde et 1, 9% (IC95%: 1, 5–2, 4) au Cameroun avait besoin d'au moins l'un des trois PA sur la base de déficiences modérées ou sévères. Le besoin total était le plus élevé pour les lunettes de distance [3, 7% (IC95%: 2, 8–4, 7) Inde; 0, 8% (IC95%: 0, 5–1, 1), Cameroun] et le plus faible pour les chaises roulantes (0, 1% dans les deux paramètres; IC95%: 0, 03–0, 3 Inde, IC95%: 0, 04‐0, 3 Cameroun). La couverture pour chaque PA était inférieure à 40%, sauf pour les lunettes de distance en Inde, où elle était de 87% (IC95%: 77, 1–93, 0). La concordance entre l'auto‐déclaration et l'évaluation clinique de la déficience du besoin en PA était faible. Par exemple, en Inde, 60% des personnes identifiées lors de l'évaluation clinique comme ayant besoin de lunettes de distance n'ont pas autodéclaré un besoin. A l'inverse, en Inde, 75% des personnes qui ont déclaré avoir besoin de lunettes de distance n'en avaient pas besoin sur la base d'une évaluation clinique de la déficience. Conclusions: Il y a un besoin élevé et une faible offre de trois PA dans deux milieux à revenu faible et intermédiaire. Les lacunes méthodologiques soulignent le besoin de méthodes d'enquête améliorées compatibles avec la classification internationale du fonctionnement, du handicap et de la santé pour estimer les besoins au niveau de la population en PA et en services connexes pour éclairer le plaidoyer et la planification.